Waste Management Based on Smart City Management by Using Internet of Things (IoT) and Artificial Intelligence (AI) Technology (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this Community Service activity is to assist the waste bank to record data in making daily reports of incoming and outgoing waste data, making reports and financial records of transaction results. Assist UPTD, TPA Management, and the Environment Agency, in receiving and managing incoming waste. Knowing the traffic of trucks entering the landfill, providing information about the status of the landfill and providing automatic records for the landfill manager. The method used in this community service activity is the lecture, discussion and direct simulation method. The results of this community service activity make it easy for waste bank officers to record and make daily reports of incoming and outgoing waste data, make reports and financial records of transaction results. Assist UPTD, TPA Management, and the Environment Agency, in receiving and managing incoming waste. Knowing the traffic of trucks entering the landfill, as well as knowing about an integrated system based on smart city management, by applying internet of things (IoT) and artificial intelligence (AI) technology. The smooth implementation of this community service activity cannot be separated from the use of complete communication media, the material delivered is appropriate to the needs of the participants, with this Community Service program, it can be a reference and example for partners who have not collaborated. Besides, this Community Service activity can change the community's negative paradigm towards waste. Based on this activity, the environmental service has the basis to provide policies, budgets and supervision regarding waste management. Besides that, with this community service activity, it changes the paradigm about the importance of waste management